Analisis Wacana Penjagaan Rumah Ibadah Agama Lain - Moh Arif Raziqy (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
Indonesia already has an apparatus that has the function of securing the activities of its citizens, but in the case of guarding this house of worship questions the dominant role of the three youth organizations. The three were NU Banser, Kokam Muhammadiyah and FPI Warriors. This paper uses the website observation method and reports on the activities of guarding houses of worship around Christmas events from 2011-2018. The approach used is the analysis of Foucault's discourse, namely the production of discourse and marginalized discourse. Kokam and Pemuda FPI experienced fluctuations in the span of the year, but the involvement of Banser covered by the media also fluctuated. In fact, such participation for Banser seems to be an annual agenda. Of course, this can not be said as a matter of fact, but it can be seen the extent to which the media interest covers.